Morphophysiological indicators of drought tolerance in sorghum hybrids - Marcos Lopes de Campos; Ignacio Aspiazú; Paulo César Magalhães; Abner José de Carvalho; Pablo Fernando Santos Alves; Arley Figueiredo Portugal (Revista Ciência Agronômica)
ABSTRACT The objective of this study was to assess the responses of sorghum hybrids to drought and select the most significant morphophysiological indicators to differentiate the hybrids grown under water deficit and well-watered conditions. Two field experiments were conducted simultaneously one under well-watered and the other under water deficit conditions after the pre-flowering stage, evaluating four contrasting grain sorghum hybrids (DKB 540, BRS 310, BRS 332, and 50A10), in a randomized block experimental design with four replications. Means were subjected to individual and joint analysis of variance, and the effects of water conditions and sorghum hybrids were compared using the F-test (p < 0.05) and the Tukey's test (p ≤ 0.05), respectively. Multivariate canonical variable analysis and Pearson correlation were also applied. Water deficit significantly reduced grain yield in 23.9%. The higher grain yields of the evaluated sorghum hybrids are associated with the higher relative chlorophyll content, photosynthetically active leaf area, panicle diameter and mass, grain mass per panicle, threshing index, and 100-grain mass, and the lower number of lodged plants. Grain mass per panicle, 100-grain mass, panicle mass, number of lodged plants, relative chlorophyll content, and leaf area are the most important indicators for explaining drought tolerance variations in grain sorghum hybrids grown under water deficit and well-watered conditions.